PREVALENCE OF VITAMIN B12 DEFICIENCY AND ITS ASSOCIATED FACTORS AMONG PATIENTS WITH TYPE 2 DIABETES ON METFORMIN IN MALAYSIA - Krishnan, Gayathri Divi; Zakria, Miza Hiryanti; Bidin, Mohamed Badrulnizam Bin Long; Yahaya, Norhayati (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION It has been proven that vitamin B12 deficiency is more common among metformin treated subjects with a variable prevalence worldwide, and this can lead to an array clinical sequelae. We evaluated the prevalence of vitamin B12 deficiency among metformin treated patients with type 2 diabetes in Malaysia. METHODOLOGY This is a cross-sectional study involving 205 patients from a Malaysian district aged 18 years old and above who have been on metformin for at least 6 consecutive preceding months. Medical history was obtained via a standardized questionnaire and all subjects had blood drawn for serum vitamin B12 levels. RESULTS Vitamin B12 deficiency was defined as serum B12 level ≤300 pg/ml (221 pmol/L). The prevalence of vitamin B12 deficiency among metformin treated patients with type 2 diabetes was 28.3% (n=58) and the mean vitamin B12 level was 457±231 pg/ml. A longer duration of diabetes and metformin use for more than 5 years were associated with an increased risk for vitamin B12 deficiency (p<0.05). The non-Malay population were at a higher risk for metformin associated vitamin B12 deficiency (p<0.001). CONCLUSION Our study suggests that patients with type 2 diabetes on metformin should be screened for vitamin B12 deficiency. This is especially so among patients with a longer duration of diabetes and those on metformin for more than five years. Also, it should be kept in mind that the non-Malay population with diabetes in Malaysia seem to be at increased risk for vitamin B12 deficiency compared to their Malay counterparts.